Needs Analysis and Design of FlipBook-Based E-Module Development with RME Model to Improve Students' Concept Understanding Ability - Sari, Nola; Khaidir, Christina (Insitut Agama Islam Negeri Kerinci, 2023)
This research is motivated by the lack of engaging learning resources for students and the absence of instructional materials in the form of E-Modules. The study is an observational research that focuses on the importance of developing teaching materials, particularly the development of Flipbook-Based E-Modules using the Realistic Mathematics Education (RME) instructional model, to enhance students' understanding of Trigonometry concepts. The method used is Research and Development (R&D), employing the 4D development model (Define, Design, Develop, Disseminate). The research utilizes a research instrument in the form of a questionnaire that is given to each 10th-grade high school student, and the questionnaire contains questions related to the needs that will be used as a reference for the development of the E-Module. Based on the questionnaire results, data analysis of the needs is obtained, which serves as a reference for the development of the E-Module. The results are then organized based on the students' needs. This development is conducted as an effort to bring about changes to the E-Module. Therefore, it is expected that this E-Module will attract students' interest in learning and improve their understanding of concepts.